Mortality of necrotizing fasciitis: relative influence of individual and hospital‐level factors, a nationwide multilevel study, France, 2007–12. (1st December 2017) - Audureau, E.; Hua, C.; de Prost, N.; Hemery, F.; Decousser, J.W.; Bosc, R.; Lepeule, R.; Chosidow, O.; Sbidian, E.
Summary: Background Necrotizing soft‐tissue infections (NSTI) are rare, life‐threatening conditions. Objectives To assess whether admitting hospital characteristics were associated with NSTI mortality. Methods We studied the French nationwide hospital discharge database (retrospective national cohort). All patients admitted in the period 2007–12 with an International Classification of Diseases 10 code of necrotizing fasciitis were eligible. We extracted data on the patients (age, sex, intensive care unit admission, comorbidities) and hospitals (public vs. private proprietary; for public hospitals, teaching, yes/no; and number of NSTI admissions, ≥ 3 NSTI cases/year, yes/no). Multivariable analyses were performed to identify independent predictors of 28‐day mortality and in‐hospital mortality using mixed logistic regression and Cox proportional hazards models, respectively. Results We identified 1537 patients (915 males) with a median age of 60 years (interquartile range 48–75), admitted to 326 hospitals, public (82%) and admitting < 3 NSTI cases/year (93%). Overall, 364 patients died [23·7%; 95% confidence interval (CI) 21·6–25·9]. Patients treated in public teaching centres with ≥ 3 NSTI cases annually had lower 28‐day mortality (adjusted odds ratio 0·68; 95% CI 0·46–0·99; P = 0·045) and in‐hospital mortality rates than patients treated in local hospitals, even after adjusting for potentially relevant individual risk factors. No significant association was found between mortality and interhospital transfer. Conclusions Our findings highlight an increased survival in teaching centres with high‐volume NSTI procedures. If confirmed in other settings, these findings reinforce the importance of expertise in early diagnosis and management of this condition.